Relationship Between Metcognition, Motivation, Locus of Control, Self-Efficacy, and Academic Achievement - Landine, Jeffrey; Stewart, John (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to examine the relationship between metacognition and certain personality variables and the role they play in academic achievement. Biggs' (1987) model of metacognition was used as the theoretical framework for the study. Measures of metacognition, motivation , locus of control, and self-efficacy were used to compare with students' indication of current academic average. These measures were adminis tered to a sample of 108 Grade 12 students in New Brunswick and Newfoundland.The results indicated significant positive relationships between metacognition, motivation, locus of control, self-efficacy, and academic average. It was concluded that metacognition and these personality variables are related to academic achievement.